(untitled) (Ukrainian Journal of Ophthalmology, 2026)
The purpose. To study changes in the macular retinal thickness in patients with diabetic retinopathy after microinvasive vitrectomy with inner limiting membrane (ILM) removal. Material and Methods. This was a retrospective analysis of spectral OCT data of the macula of eighty-eight eyes (77 patients) after 23 gauge vitrectomy for proliferative diabetic retinopathy. The surgeries were performed at National Centre of Ophthalmology named after acad. Zarifa Aliyeva, Baku, Azerbaijan, in the period between 2010 and 2015. Study group comprised fifty-nine eyes in which vitrectomy was performed with ILM removal; Control group comprised thirty eyes in which ILM was not removed during the surgery. ILM was peeled using ILM forceps (Alcon, the USA) after brilliant blue G (BBG) staining. For statistical analysis, we used three Cirrus-HD OCT measurements: central (1 mm), inner temporal (1-3 mm), and inner nasal (1-3 mm) retinal thickness. Results. At 12 months after surgery, the mean macular thickness in the inner temporal subfield was much thinner in the eyes with ILM removal than in those without ILM removal, 279±51.9 ?m vs. 332±93.8 ?m, (p=0,002), respectively. The macular thickness in the central, foveolar subfield almost did not differ in different groups as well as the thickness in the inner nasal subfield (p>0.05 in both cases). Since there was not a healthy paired eye, we compared our data with the normative data obtained from the paper by Liu et al [2011], in which Cirrus HD OCT showed the macular thickness in the inner temporal subfield equal to 313.4±18.5 ?m in diabetic patients without retinopathy signs, which was significantly higher than in our patients after vitrectomy with ILM removal (295±43.1 ?m, p=0.002). And the macular thickness in the nasal and central foveal subfields did not differ significantly from our data. Conclusions. We revealed thinning of the macular temporal subfield after vitrectomy with ILM removal not only in patients with diabetic macular edema but also with tractional retinal detachment and vitreous hemorrhage. Our data confirm, once again, a universal character of the asymmetric changes in the macular thickness in the temporal and nasal subfields after vitrectomy with ILM removal for various pathological changes in the retina. However, to clarify the practical meaning of this phenomenon, the further functional investigations are required.